Adhesive dentistry sensory stimulus technique as a neuromechanism for the treatment of orofacial pain associated to temporomandibular disorders: Case study - Miguel Pais Clemente; Asdrúbal Pinto; Fernando Milheiro; Teresa F. Costa; Andre Moreira; Ricardo Vardasca; Pedro A. Pereira; Joaquim Mendes; M. Dulce Madeira; José Manuel Amarante (Journal of Oral Biology and Craniofacial Research)
Purpose: The authors intend, by presenting a case study, emphasize the neuromodulation process of orofacial pain induced by the stimulation of the sensory and motor stimulation of the trigeminal nerve, which can play an important role on pain modulation. Materials and methods: A 25 year-old woman presenting orofacial pain was referred to the stomatology service at the Centro Hospitalar do Porto. After collecting the patient's anamnesis, the thermographic camera FLIR i7 was used to record the thermal status of the orofacial structures, before the adhesive dentistry sensory stimulus protocol, after 45 minutes, and after one week. Results: This study suggests the relation of adhesive dentistry sensory stimulus technique in the neuromodulation of orofacial pain and its association with the temporomandibular disorders . As the tongue senses the stimulus of the resin composite placed on the palatal surface of the 1st premolar, 2nd premolar and 1st molar of the maxilla, this can promote and induce an effect regarding a peripheral nerve neuromodulation resulting in a blockage of the nociceptive trigeminal pathway from temporomandibular disorders. Conclusion: Orofacial pain is a common complaint among the patients that come to a dentistry appointment, which may have different diagnosis and treatments. A positive effect on the patient's symptomatology was confirmed clinically on subsequent dental appointments and monitored by infrared thermography.